"A Most Valuable Curiosity": Music Manuscripts, Authorship, Composition, and Gender at the Ephrata Cloister in Eighteenth-Century Pennsylvania. Issue 4 (November 2022) - Herbert, Christopher
Abstract: The 1746 Ephrata Codex, a 972-page music manuscript in the Library of Congress, is the central document of this study, which locates and identifies several eighteenth-century composers who were solitary sisters and brothers of the Ephrata Cloister in Lancaster County, Pennsylvania. Ephrata was an insular, mainly celibate, Pietist, Sabbatarian, ascetic community, which, at its height in the 1740s and 1750s, was home to approximately 300 individuals. Like many German diaspora societies in colonial Pennsylvania, it produced devotional prints and manuscripts. Ephrata is unique because most of its spiritual texts and music were written by and for its inhabitants. More than 130 extant Ephrata music manuscripts in libraries, archives, and collections in the United States and United Kingdom comprise a corpus of over 1, 500 hymns, composed according to rules mandated in an original music theory treatise. The concept of authorship at Ephrata was complicated: Communal creative activity frequently existed alongside calls for individual recognition, evidenced by name attributions found in printed hymnals and music manuscripts. The solitary sisters' agency and creative activity at Ephrata brings an added nuance to the discussion of authorship and credit, drawing attention to the contributions of women as creators, a notable exception to the male-dominated sieve of music history. The 2020 release of Voices in the Wilderness, an album of new Ephrata hymn transcriptions, is connected to this article. Recorded in the Ephrata Meetinghouse, or "Saal, " the room for which the music was composed, it provides a new perspective on Ephrata's composers, compositional methods, and performance practice.